Spatial and temporal fluctuation of phytoplankton functional groups in a tropical reservoir - doi: 10.4025/actascibiolsci.v35i3.12988 (Acta Scientiarum. Biological Sciences, 2013)
Along the horizontal axis of reservoirs are generally recognized three zones (fluvial, transition and lacustrine) with distinct hydrodynamic and physical, chemical and biological properties. Quarterly samplings were conducted in 2002, in the limnetic region from each zone, at different depths of a tropical reservoir. To test the hypothesis that highest biomass (biovolume) of phytoplankton are found in the transition zone, the PERMANOVA analysis was realized. 106 taxa were recorded. Significant differences between biovolume values of the three zones were not verified (pseudo F = 0,89; p = 0,55). Higher values of biomass were obtained in lacustrine and transition zones of the reservoir. The functional group (FG) N (Cosmarium spp.) was dominant in these zones, in rain period, and related to low phosphorus concentration, high transparency and water column stability. Low biovolume values in reservoir characterized oligotrophic conditions in all zones of the reservoir, most of the period. The dominance of FGs Y, Lo, E, P and A, as evidenced by the CCA, was associated with low light availability and higher nutrients concentrations.